Effect of Freeze-Thaw Cycles on Shear Strength Properties of Loess Reinforced with Lignin Fiber - Zhongnan Gao; Xiumei Zhong; HaiPing Ma; Fuqiang Liu; Jinlian Ma; Qian Wang (Geofluids)
Freeze-thaw cycles caused by climate change can change the structure and strength of the soil. In seasonally frozen soil areas, the use of improved loess as a filling material must consider the effects of freeze-thaw cycles. With the increasingly severe global environmental problems, the search for suitable new environmental protection improvement materials has become one of the hotspots in soil performance improvement research. The purpose of this paper is to use lignin fiber to improve the engineering performance and freeze-thaw resistance of loess and to reduce the negative impact of engineering construction on the environment of the loess area. Based on a series of triaxial shear tests, the effects of freeze-thaw cycles on the stress-strain relationship, shear strength, and Mohr-Coulomb’s strength parameters of loess reinforced with lignin fiber were analyzed. Combined with the volume change and microstructure characteristics of fiber-reinforced loess before and after the freeze-thaw cycles, the reasons for the effects of the freeze-thaw cycles on the shear strength characteristics of fiber-reinforced loess are discussed. The research results showed that after 15 freeze-thaw cycles, the shear strength of loess reinforced with 1% fiber increased by 0.15%, 2.05%, and 1.35% at 80, 140, and 200 kPa, respectively. The shear strength of the reinforced loess with other fiber contents decreases to different degrees, and the maximum reduction ratio can reach 9.54%. Freeze-thaw cycles changed the variation of shear strength and strength parameters with fiber content. When the fiber content is less than 1%, the shear strength, cohesion, and friction angle of fiber-reinforced loess increase the fastest after freeze-thaw cycles. When the fiber content is 1%, the overall destruction effect of freeze-thaw cycles on fiber-reinforced loess is inhibited, and the soil has the best freeze-thaw resistance.